Red Blood Cell Alloimmunization among the Transfusion Recipients at Sanglah General Hospital, Denpasar, Bali: A Preliminary Study - Sianny Herawati; Usi Sukorini; Teguh Triyono (Journal of Global Pharma Technology, 2018)
Background Red blood cell (RBC) alloimmunization is the formation of alloantibodies among the recipientswhich is related to the frequency of antigen-positive blood transfusion received by the recipient. The difficultyto obtain compatible RBC and a higher risk of hemolytic transfusion reactions due to alloimmunizationbecome a challenge in clinical practice. Objectives: This study aims to analyze the characteristics of RBCalloantibodies in the recipient following transfusion at Sanglah General Hospital, Bali, as a preliminary study.Methods A cross sectional study was conducted among 40 recipients with a history of RBC transfusion atleast 3 times and willing to participate in this study from December 2016 to March 2017 at Sanglah General Hospital. Data were analyzed using SPSS ver. 16 software to determine the prevalence of study. Resultsmost recipients were 46 – 65 years (55%). In addition, most recipients were caused by hematology disorder (57.5%), female (52.5%), and O-Rhesus D positive (52.5%). RBC alloantibodies detected in 5% of recipients,all of them were multiple alloantibodies, such as anti-K antibodies (5%), anti-Kp a (5%), anti-E (2.5%), anti-C w(2.5%), anti-Lu a (2.5%) and anti-M (2.5%). Those alloantibodies only found in 46 – 65 years age group.Conclusion the first preliminary study regarding RBC alloimmunization in Bali was found contributed by anti-K,anti Kp a , anti-E, anti-C w , anti-Lu a , and anti-M. The results suggest that erythrocyte antigen phenotypes can beperformed further, particularly the Kell antigen to prevent alloimmunization. However, future studies withbigger samples are needed to determine the incidence of RBCalloimmunization among transfusion recipients in Bali.Keywords: Alloimmunization, Red blood cells, Transfusion recipients.